2013
DOI: 10.1093/carcin/bgt306
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of magnolin on ERKs inhibits Ras/ERKs/RSK2-signaling-mediated neoplastic cell transformation

Abstract: Mitogen-activated protein kinases play a key role in cell proliferation, cell cycle progression and cell transformation, and activated Ras/extracellular signal-regulated kinases (ERKs)/ribosomal S6 kinase 2 (RSK2) signaling pathways have been widely identified in many solid tumors. In this study, we found that magnolin, a compound found in the Magnolia species, directly targeted and inhibited ERK1 and ERK2 kinase activities with IC50 values of 87 and 16.5 nM by competing with adenosine triphosphate in an activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 25 publications
5
46
0
Order By: Relevance
“…Moreover, we confirmed that magnolin suppressed ATF1 phosphorylation only in TOV‐112D cells, not in SKOV3 cells, under normal cell culture conditions (Figure E). Taken together with the results in our previous study, these results demonstrate that molecular targeting of ERK1 and ERK2 with magnolin can suppress ovarian cancer cell lines harboring a general MAPK signaling cascade such as TOV‐112D. These results also suggest that cells containing a bypass signaling pathway of ERK1/2 may induce chemoresistance against therapeutic compounds that target RSK upstream signaling molecules in Ras/Raf/MEKs/ERKs signaling axis.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, we confirmed that magnolin suppressed ATF1 phosphorylation only in TOV‐112D cells, not in SKOV3 cells, under normal cell culture conditions (Figure E). Taken together with the results in our previous study, these results demonstrate that molecular targeting of ERK1 and ERK2 with magnolin can suppress ovarian cancer cell lines harboring a general MAPK signaling cascade such as TOV‐112D. These results also suggest that cells containing a bypass signaling pathway of ERK1/2 may induce chemoresistance against therapeutic compounds that target RSK upstream signaling molecules in Ras/Raf/MEKs/ERKs signaling axis.…”
Section: Resultssupporting
confidence: 84%
“…The Ras/Raf/MEKs/ERKs/RSK2 signaling pathway has an important role in cell proliferation and cancer development by stimulation of growth factors . Our previous results demonstrated that inhibition of ERK1 and ERK2 by magnolin suppresses G1/S cell‐cycle transition in premalignant JB6 Cl41 cells . Therefore, based on the results presented in Figure and Table , we hypothesized that magnolin might differentially inhibit cell‐cycle arrest in TOV‐112D and SKOV3 ovarian cancer cells.…”
Section: Resultsmentioning
confidence: 89%
“…Epimagnolin (Figure A), a natural lignan compound abundantly found in Magnolia flos, has a very similar chemical structure to those of magnolin and aschantin . Our previous studies demonstrated that magnolin and aschantin suppressed tumor promoter‐induced carcinogenesis and cancer cell proliferation . Although epimagnolin is structurally similar to magnolin, the efficacy of epimagnolin on carcinogenesis and the molecular targets of epimagnolin have not been clearly elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Epimagnolin has a chemical structure similar to those of magnolin and aschantin . Recently, our research group found that magnolin targets ERK1 and ERK2 with 87 and 16.5 nM IC 50 values, respectively . Moreover, although aschantin also has a very similar chemical structure to that of magnolin, aschantin targets mTOR kinase with an IC 50 of approximately 400 nM without affecting ERK1 and ERK2 activity .…”
Section: Introductionmentioning
confidence: 95%
“…Fargesin exhibits additional biological activities, including β1-adrenergic receptor antagonistic and cardioprotective effects [13], stimulation of basal glucose uptake and glucose transporter-4 translocation in muscle cells [14], treatment of dyslipidemia and hyperglycemia in high-fat diet-induced obese mice via activation of Akt and 5′-adenosine monophosphate-activated protein kinase in white adipose tissue [15], and antihypertensive effects in 2K1C hypertensive rats [16]. Magnolin also inhibits cancer cell migration, invasion, and growth [17,18,19] and ameliorates contrast-induced nephropathy via antioxidation and antiapoptosis in rats [20]. …”
Section: Introductionmentioning
confidence: 99%